Cellular compartmentation follows rules: The Schnepf theorem, its consequences and exceptions: A biological membrane separates a plasmatic from a non‐plasmatic phase. (16th June 2017) - Moog, Daniel; Maier, Uwe G.
Abstract : Is the spatial organization of membranes and compartments within cells subjected to any rules? Cellular compartmentation differs between prokaryotic and eukaryotic life, because it is present to a high degree only in eukaryotes. In 1964, Prof. Eberhard Schnepf formulated the compartmentation rule (Schnepf theorem), which posits that a biological membrane, the main physical structure responsible for cellular compartmentation, usually separates a plasmatic form a non‐plasmatic phase. Here we review and re‐investigate the Schnepf theorem by applying the theorem to different cellular structures, from bacterial cells to eukaryotes with their organelles and compartments. In conclusion, we can confirm the general correctness of the Schnepf theorem, noting explicit exceptions only in special cases such as endosymbiosis and parasitism. Abstract : The compartmentation rule by Eberhard Schnepf (Schnepf theorem) was formulated more than 50 years ago. In its quintessence, it posits that a biological membrane separates a plasmatic form a non‐plasmatic phase. The theorem addresses important biological questions including cellular and compartmental evolution as well as endosymbiosis and intracellular parasitism.